Differential Kinetics in Alteration and Recovery of Cognitive Processes from a Chronic Sleep Restriction in Young Healthy Men - Rabat, Arnaud; Gomez-Merino, Danielle; Roca-Paixao, Laura; Bougard, Clément; Van Beers, Pascal; Dispersyn, Garance; Guillard, Mathias; Bourrilhon, Cyprien; Drogou, Catherine; Arnal, Pierrick J.; Sauvet, Fabien; Leger, Damien; et al. (Frontiers in Behavioral Neuroscience, 2016)
Chronic sleep restriction (CSR) induces neurobehavioral deficits in young and healthy people with a morning failure of sustained attention process. Testing both the kinetic of failure and recovery of different cognitive processes (i.e. attention, executive) under CSR and their potential links with subject’s capacities (stay awake, baseline performance, age) and with some biological markers of stress and anabolism would be useful in order to understand the role of sleep debt on human behavior. Twelve healthy subjects spent 14 days in laboratory with 2 baseline days (B1 and B2, 8h TIB) followed by 7 days of sleep restriction (SR1-SR7, 4h TIB), 3 sleep recovery days (R1-R3, 8h TIB) and 2 more ones 8 days later (R12-R13). Subjective sleepiness (KSS), maintenance of wakefulness latencies (MWT) were evaluated 4 times a day (10:00, 12:00 a.m. and 2:00, 4:00 p.m.) and cognitive tests were realized at morning (8:30 a.m.) and evening (6:30 p.m.) sessions during B2, SR1, SR4, SR7, R2, R3 and R13. Saliva (B2, SR7, R2, R13) and blood (B1, SR6, R1, R12) samples were collected in the morning. Cognitive processes were differently impaired and recovered with a more rapid kinetic for sustained attention process. Besides, a significant time of day effect was only evidenced for sustained attention failures that seemed to be related to subject’s age and their morning capacity to stay awake. Executive processes were equally disturbed/recovered during the day and this failure/recovery process seemed to be mainly related to baseline subject’s performance and to their capacity to stay awake. Morning concentrations of testosterone, cortisol and α-amylase were significantly decreased at SR6-SR7, but were either and respectively early (R1), tardily (after R2) and no recovered (R13). All these results suggest a differential deleterious and restorative effect of CSR on cognition through biological changes of the stress pathway and subject’s capacity (ClinicalTrials-NCT01989741).